A critical review of research into mental health consumers' perspectives on their physical health: Is there an absence of consumers in the design, conduct, analysis and reporting of this research? - Green, Chloe R.; Elwyn, Rosiel; Hill, Nicholas; Johnston-Ataata, Kate; Kokanović, Renata; Maylea, Chris; McLoughlan, Grace; Roberts, Russell; Thomas, Stuart D. M. (Frontiers in Public Health, 2023)
We conducted a critical review, using systematic methods, of the literature examining mental health consumer perspectives on their physical and mental health in academic research published between 2005-2021. This review examined the inclusion, extent, type and centrality of consumer perspectives regarding their mental and physical health. The search produced 1865 papers from which 116 met the inclusion criteria. Studies predominantly focused on consumers’ individual experiences of their physical and mental health, including but not limited to their understandings and experiences of medication and associated risk factors. They also captured some social aspects of mental health consumers’ physical health, including factors that impacted individual agency, stigma, and social and interpersonal factors. Structural factors affecting physical and mental health, such as accessibility of services and financial constraints, were also identified. The review revealed that in comparison to clinician perspectives, the direct representation of consumer perspectives was lacking. Similarly, while clinician and carer perspectives on structural factors were investigated, the consumer perspective in this area was missing. The review also found few genuine codesigned or coproduced research studies. To better identify and respond to the health needs as prioritised by consumers, this paper argues it is imperative that future studies prioritise codesigned and coproduced research. It is argued that a focus on ‘services as provided’ rather than ‘services as received’ has contributed to a lack of progress in addressing the life expectancy gap for consumers. It is recommended that journals, ethics committees and research policy organisations develop guidelines and standards to inform best practice in research on consumer perspectives and experience and to support the implementation of codesigned and/or coproduced approaches in future research. Respecting and including consumers as equal partners in the research process will lead to more meaningful insights to inform policy and practice and reduce the life expectancy gap for people living with mental health concerns.